P62 inhibits IL-1β release during Salmonella Typhimurium infection of macrophages - Hos, Nina Judith; Fischer, Julia; Murthy, Ambika M. V.; Hejazi, Zahra; Krönke, Martin; Hos, Deniz; Robinson, Nirmal (Frontiers in Cellular and Infection Microbiology, 2025)
Macrophages are critical for the innate immune defense against the facultative intracellular Gram-negative bacterium Salmo ella enterica serovar Typhimurium. Following phagocytosis by macrophages, S. Typhimurium activates cytoplasmic NLRC3 and NLRP4 inflammasomes, which share the adaptor ASC, resulting in the secretion of the pro-inflammatory cytokine IL-1β. To prevent excessive inflammation and tissue damage, inflammatory signaling pathways are tightly controlled. Recently, autophagy has been suggested to limit inflammation by targeting activated inflammasomes for autophagic degradation. However, the importance of the autophagic adaptor Sequestome-1 (hereafter, p62) for regulating inflammasome activation remains poorly understood. We report here that p62 restricts inflammasome availability and subsequent IL-1β secretion in macrophages infected with S. Typhimurium by targeting the inflammasome adaptor ASC for autophagic degradation. Importantly, loss of p62 resulted in impaired autophagy and increased IL-1β secretion, as well as IL-10 and IFN-β release. In summary, our results demonstrate a novel role for p62 in inducing autophagy and balancing major pro- and anti-inflammatory signaling pathways to prevent excessive inflammation during S. Typhimurium infection of macrophages.